Sweet Success or Sour Struggles? Efficiency of the East Java Sugar Industry - Fichrie Fachrowi Adli; Salsabil Rifqi Qatrunnada; Yan Cerin Satmoko (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2025)
East Java is one of the major sugar-producing provinces in Indonesia, home to sugar firms that have been operating for more than a century. However, the annual increase in sugar consumption has not been matched by a corresponding increase in production. Therefore, this study examines the efficiency of the sugar industry in East Java using an output-oriented approach, which separates persistent and transient inefficiencies, as well as an input-oriented approach that examines the use of machinery and energy, along with the determinants of inefficiency. This study applies the Stochastic Frontier Analysis (SFA) method, utilizing microdata from Statistik Industri (SI). The results reveal a trend of decreasing returns to scale in the sugar industry in East Java. Inefficiency in the sugar industry is primarily driven by persistent inefficiency, indicating the presence of structural problems. Furthermore, production inefficiency was found to be higher than inefficiency related to the use of machinery and energy. Export intensity has been shown to reduce inefficiencies in production, machinery use, and energy use. Additionally, greater reliance on imported materials contributes to lower energy inefficiency, while increased market concentration tends to exacerbate production inefficiency.